Further validation of the BILAG disease activity index in patients with systemic lupus erythematosus. - Stoll, T (1996)
OBJECTIVE: To examine the association among the BILAG disease activity index components and their relations with global assessments, health status, and laboratory tests with regard to the validity of the BILAG index. METHODS: A cross sectional study of consecutive patients with systemic lupus erythematosus (SLE) attending a specialist lupus outpatient clinic between July 1994 and February 1995. The internal consistency of the British Isles Lupus Assessment Group (BILAG) index-a disease activity assessment system for SLE patients, based on the principle of the physician's intention to treat-was examined using Cronbach's coefficient alpha. The association of the components of the BILAG index with health status as measured with the MOS Short Form 20 (SF-20), with patients' and doctors' global assessments of patient wellbeing and with laboratory tests was analysed with Spearman rank correlations. RESULTS: 133 female and eight male patients, age 20.1 to 88.7 years (mean 41.1, SD 12.5), were included. With few exceptions, the components of the BILAG index which reflect disease activity in different organ systems were not associated with each other. With the exception of the mucocutaneous component, we found a significant relation between all components of BILAG and global assessment of patient wellbeing, health status, erythrocyte sedimentation rate, or serum C3 level. CONCLUSIONS: The study confirms the validity of all but the mucocutaneous component of the BILAG index. However, disease activity in different organ systems in SLE does not follow a common pattern. Thus the individual BILAG components should be used rather than the total BILAG score as a primary endpoint in clinical and epidemiological studies. To capture the total effect of SLE on an individual measures of disease activity, damage, and health status are all needed.